Neural correlates of the behavioral-autonomic interaction response to potentially threatening stimuli - Farrow, Tom F.; Johnson, Naomi K.; Hunter, Michael D.; Barker, Anthony T.; Wilkinson, Iain D.; Woodruff, Peter W. (Frontiers in Human Neuroscience, 2013)
Subjective assessment of emotional valence is typically associated with both brain activity and autonomic arousal. Accurately assessing emotional salience is particularly important when perceiving threat. We sought to characterise the neural correlates of the interaction between behavioural and autonomic responses to potentially threatening visual and auditory stimuli. 25 healthy male subjects underwent fMRI scanning whilst skin conductance responses (SCR) were recorded. 180 pictures, sentences and sounds were assessed as ‘harmless’ or ‘threatening’. Individuals’ stimulus-locked, phasic SCRs and trial-by-trial behavioural assessments were entered as regressors into a flexible factorial design to establish their separate autonomic and behavioural neural correlates, and convolved to examine psycho-autonomic interaction effects. Across all stimuli, ‘threatening’, compared with ‘harmless’ behavioural assessments were associated with mainly frontal and precuneus activation with specific within-modality activations including bilateral parahippocampal gyri (pictures), bilateral anterior cingulate cortex and frontal pole (sentences) and right Heschl’s gyrus and bilateral temporal gyri (sounds). Across stimulus modalities SCRs were associated with activation of parieto-occipito-thalamic regions, an activation pattern which was largely replicated within-modality. In contrast, psycho-autonomic interaction analyses revealed modality-specific activations including right fusiform / parahippocampal gyrus (pictures), right insula (sentences) and mid-cingulate gyrus (sounds). Phasic SCR activity was positively correlated with an individual’s propensity to assess stimuli as ‘threatening’. SCRs may modulate cognitive assessments on a ‘harmless - threatening’ dimension, thereby modulating affective tone and hence behaviour.